NATIONAL CULTURE AND NATIONAL VALUES OF THE UZBEK PEOPLE THROUGH THE EYES OF FOREIGN EXPERTS (International conference on multidisciplinary science, 2023)
in this article, the national culture and national values of the Uzbek people are widely promoted through the eyes of foreign experts, in the era of globalization and technology, Uzbekistan cherishes its rich cultural heritage, at the same time trying to introduce it into time. From museums and cultural centers, which preserve and promote folk applied art, to educational programs and festivals aimed at studying and developing the cultural heritage of the navqiran generation, to the need to be widely promoted in our country.